Formic acid enhances whole-plant mulberry silage fermentation by boosting lactic acid production and inhibiting harmful bacteria - Hao, Lihong; Jiang, Fugui; Wang, Yanping; Wang, Huaizhong; Hu, Hongmei; You, Wei; Hu, Xin; Cheng, Haijian; Wang, Cheng; Song, Enliang (Frontiers in Microbiology, 2024)
Mulberry has also been regarded as a valuable source of forage for ruminants. This study was developed to investigate the impact of four additives and combinations thereof on fermentation quality and bacterial communities associated with whole-plant mulberry silage. Control fresh material (FM) was left untreated, while other groups were treated with glucose (G, 20 g/kg FM), a mixture of Lactobacillus plantarum and L. buchneri (L, 106 CFU/g FM), formic acid (A, 5 mL/kg FM), salts including sodium benzoate and potassium sorbate (S, 1.5 g/kg FM), a combination of G and L (GL), a combination of G and A (GA), or a combination of G and S (GS), followed by ensiling for 90 days. Dry matter content in the A, S, GA, and GS groups was elevated relative to the other groups (p < 0.01). Relative to the C group, all additives and combinations thereof were associated with reductions in pH and NH3-N content (p < 0.01). The A groups exhibited the lowest pH and NH3-N content at 4.23 and 3.27 g/kg DM, respectively (p < 0.01), whereas the C groups demonstrated the highest values at 4.43 and 4.44 g/kg DM, respectively (p < 0.01). The highest levels of lactic acid were observed in the GA and A groups (70.99 and 69.14 g/kg DM, respectively; p < 0.01), followed by the GL, L, and GS groups (66.88, 64.17 and 63.68 g/kg DM, respectively), with all of these values being higher than those for the C group (53.27 g/kg DM; p < 0.01). Lactobacillus were the predominant bacteria associated with each of these samples, but the overall composition of the bacterial community was significantly impacted by different additives. For example, Lactobacillus levels were higher in the G, A, and GA groups (p < 0.01), while those of Weissella levels were raised in the L, GL, and GS groups (p < 0.01), Pediococcus levels were higher in the A and GA groups (p < 0.01), Enterococcus levels were higher in the G and S groups (p < 0.01), and Lactococcus levels were raised in the S group (p < 0.01). Relative to the C group, a reduction in the levels of undesirable Enterobacter was evident in all groups treated with additives (p < 0.01), with the greatest reductions being evident in the A, S, GA, and GS groups. The additives utilized in this study can thus improve the quality of whole-plant mulberry silage to varying extents through the modification of the associated bacterial community, with A and GA addition achieving the most efficient reductions in pH together with increases in lactic acid content and the suppression of undesirable bacterial growth.